Efficacy and safety of eltrombopag in the treatment of severe chronic immune thrombocytopenia in children of China: A single-center observational study. (August 2019) - Cheng, Xiaoling; Yan, Kuo; Ma, Jingyao; Chen, Zhenping; Zhao, Libo; Wang, Xiaoling; Wu, Runhui
The treatment of severe chronic immune thrombocytopenia (SCITP) in pediatric patients is challenging. We evaluated the clinical efficacy and safety of eltrombopag in children with SCITP in China. This observational study was carried out at the Hematology Oncology Center, Beijing Children's Hospital between April 2017 and July 2018. Patients with SCITP who had at least 12 weeks of eltrombopag treatment and follow-up data were included. Baseline data, such as age, drug dosage, pre-study platelet count, concomitant medications, and bleeding severity, were collected. Treatment response rates, durable response rates, bleeding events, and adverse events were assessed during eltrombopag therapy for at least 12 weeks. The median duration of eltrombopag therapy was 16 (12–48) weeks. The overall, complete, and partial response rates were 75% (15/20), 35% (7/20), and 40% (8/20), respectively. The durable response rate was 70% (14/20). No serious bleeding events or serious adverse events occurred during the study period. Eltrombopag appears to be effective and safe in children with SCITP, although additional research is needed to confirm this.